Studying abroad: the role of consumer cosmopolitanism in the enrolment decisions - Salomão, Miriam Taís; Silva, Susana Costa; Côto, José Ricardo (Young consumers, 2022)
Purpose Cosmopolitans transcend their local boundaries by interacting and actively seeking other cultures, and the applications of these characteristics to consumption behaviour is called consumer cosmopolitanism. To outline inferences on what school leavers would experience, consider or do when planning to study abroad, this paper aims to examine people who have experienced Erasmus concerning the relationship between their level and type of consumer cosmopolitanism and the decisions related to enrolling in the Erasmus programme, which include the decision itself, motivations, choice of destination, pursuing cultural differences and search for different levels of globalisation. Design/methodology/approach After proposing a conceptual model, data were collected by surveying undergraduate or postgraduate students. Then a set of multivariate analyses were developed to validate the hypotheses. Findings Contrarily to what could be expected, results indicate that consumer cosmopolitanism decreases the likelihood for students to enrol on the programme. Additionally, three types of consumer cosmopolitanism were found: low, cultural and high cosmopolitans. According to results, low cosmopolitans display lower likelihoods of enrolment than the other two types. This evidence supports that intention to enrol is not always a good predictor of behaviour and that a gap is proven here as well. This study also suggests that cosmopolitan consumers do not reveal a preference for countries with similar/different cultures or levels of globalization to that of their own country, but, conversely, experiencing a different culture remains one of the leading motivations for these consumers. Originality/value Although cosmopolitanism has been extensively studied in different research fields, its link with the decisions on studying abroad has barely been explored.